Role of histopathological and microbiological investigations for a definitive diagnosis of benign sinonasal masses: a tertiary care institute study - Maan, Arvinder Singh; Bhagat, Ruchika; Navneet (International Journal of Research in Medical Sciences, 2024)
Background: This research aimed to study the clinical presentation of various sino nasal masses (SNM), to study the importance of Histopathological and microbiological investigations in making diagnosis of SNM and to study the correlation between clinical, radiological, histopathological, and microbiological findings of SNM. Methods: In the present study 50 patients attending the ENT outpatient department with clinical evidence of nasal mass were selected based on inclusion and exclusion criteria. Patients were examined clinically and radiologically followed by surgical intervention. Histopathological and microbiological examination was done to make a definitive diagnosis. Results: Majority of cases were from 21-40 years age group (66%) with male preponderance. Nasal obstruction was most common symptom 45 (90%) followed by nasal discharge 43(86%). On histopathology highest incidence was of inflammatory polyps 22 (44%) followed by allergic polyps 14(28%) and non-invasive fungal sinusitis (NIFS) 11 (22%) respectively. Microscopically in KOH, fungal elements, yeast and hyphae were seen in total 11 (22%) cases and with SDA, Aspergillus niger was seen in 7 (14%) cases, Candida albicans in 3 (6%) and both in 1 (2%) case. Correlation of provisional diagnosis with HPE was found to be highly significant. Conclusions: It was observed that histopathological and microbiological examination is irreplaceable as both are the “GOLD STANDARD” for making a definitive diagnosis.